Do Solid Pseudopapillary Neoplasms Shrink After Menopause?. Issue 6 (August 2015) - Kurokawa, Sachiko; Hirabayashi, Kenichi; Hadano, Atsuko; Yamada, Misuzu; Tajiri, Takuma; Nakamura, Naoya
<x xml:space="preserve">Abstract</x> Supplemental digital content is available in the text.